Rapid micromethod for the purification of Escherichia coli ribonucleic acid polymerase and the preparation of bacterial extracts active in ribonucleic acid synthesis. - Gross, C (1976)
A rapid micromethod is described for the preparation of nucleic acid-free extracts from Escherichia coli that involves precipitation with polyethylene glycol. Extracts can be prepared from growing cells in 75 min by three short, low-speed centrifugations. The extract did not inhibit added purified ribonucleic acid (RNA) polymerase, suggesting that major inhibitors of RNA synthesis had been removed. This extract should be ideal for assessing the properties of mutant RNA polymerases. The rapid chromatography of the extracts with step elution from deoxyribonucleic acid- and diethylaminoethyl-cellulose columns resulted in high yields of substantially pure RNA polymerase. We used this technique to purify 35S-labeled RNA polymerase. This system should find application for the purification of small quantities of other bacterial RNA polymerases that share the general chromatographic properties of E. coli RNA polymerase.